New Approach to Religion: An Outlook to Edward E. Evan Pritchard's Theory of Religion - Fanani, Bakhruddin (UIN Maulana Malik Ibrahim Malang, 2006)
Sir Edward Evan Evans-Pritchard is a famous British anthropologist, especially known for his research on African cultures. He earned the British knighthood in 1971. His interest is directed at the study of social anthropology and the kinship system of various African tribes, especially Zande and Nuer in Southern Sudan. His two books on these two tribes, Witchraftt, Oracles, Old Magic Among the Azande (1973) and the Nuer (1940) made his argument even more popular and earned an academic award in his field. Pritchard asserted that to draw better explanation on religion, scholars should work more on research outside libraries and theological text and report. A religion should be explained in a way that is developed by its believers, not from orients and theologians teachings. Sir Edward Evan Evans-Pritchard adalah seorang antropolog Inggris yang terkenal, yang terkenal dengan penelitiannya tentang budaya Afrika. Dia mendapatkan gelar ksatria Inggris pada tahun 1971. Minatnya diarahkan pada studi antropologi sosial dan sistem kekerabatan dari berbagai suku Afrika, terutama Zande dan Nuer di Sudan Selatan. Dua bukunya tentang dua suku ini, Witchraftt, Oracles, Old Magic Diantara theAzande (1973) dan Nuer (1940) membuat argumennya semakin populer dan mendapat penghargaan akademis di bidangnya. Pritchard menegaskan bahwa untuk menarik penjelasan lebih baik tentang agama, para ilmuwan harus lebih banyak mengerjakan penelitian di luar perpustakaan dan teks teologis dan laporannya. Sebuah agama harus dijelaskan dengan cara yang dikembangkan oleh orang-orang percaya, bukan dari orientasi dan ajaran teolog.